Does the UKCAT predict performance in medical and dental school? A systematic review. Issue 1 (22nd January 2021) - Greatrix, Rachel; Nicholson, Sandra; Anderson, Susan
Abstract : Objectives: For the first time, this systematic review provides a summary of the literature exploring the relationship between performance in the UK Clinical Aptitude Test (UKCAT) and assessments in undergraduate medical and dental training. Design: In accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis, relevant studies were identified through systematic literature searches. Electronic searches were carried out on EBSCO, EMBASE, Educational Resources Information Centre, SCOPUS, Web of Knowledge. Studies which included the predictive validity of selection criteria including some element of the UKCAT were considered. Results: 22 papers were identified for inclusion in the study. Four studies describe outcomes from dental programmes with limited results reported. 18 studies reported on relationships between the UKCAT and performance in undergraduate medical training. Of these, 15 studies reported relationships between the UKCAT cognitive tests and undergraduate medical assessments. Weak relationships (r=0.00–0.29) were observed in 14 of these studies; four studies reported some moderate relationships (r=0.30–0.49). The strongest relationships with performance in medical school were observed for the UKCAT total score and the verbal reasoning subtest. Relationships with knowledge-based assessments scores were higher than those for assessments of skills as the outcome. Relationships observed in small (single and double centre studies) were larger than those observed in multicentre studies. Conclusion: The results indicate that UKCAT scores predict performance in medical school assessments. The relationship is generally weak, although noticeably stronger for both the UKCAT total score and the verbal reasoning subtest. There is some evidence that UKCAT continues to predict performance throughout medical school. We recommend more optimal approaches to future studies. This assessment of existing evidence should assist medical/dental schools in their evaluation of selection processes.